Gastrointestinal Presentation of Eosinophilic Granulomatosis with Polyangiitis, Formerly Churg-Strauss Syndrome: A Case Report - Muhammad Umair Tayyub; Arsh Gupta; Rabia Ashraf; Meenal Gupta; Priyan Tantrige; Howard Curtis; Vinod Audimoolam (Case Reports in Gastroenterology)
Introduction: Some of the most common presentations of gastrointestinal diseases are nausea, vomiting, and generalized abdominal pain. These symptoms could also be associated with other diseases and require a structured approach to the specific diagnosis. Eosinophilic granulomatosis with polyangiitis (EGPA), also known as Churg-Strauss syndrome, is a small and medium-sized vessel vasculitis that can affect any body system and present with a wide range of symptoms and atypical presentation. Therefore, diagnosis of this condition may not always be straightforward. Case Presentation: This case report presents a challenging case of a young man presenting with symptoms of abdominal pain, nausea, vomiting and non-specific symptoms of lethargy and fatigue. The case describes overlapping features with granulomatosis with polyangiitis (GPA) and anti-neutrophil cytoplasmic antibodies (ANCA)-positive and -negative vasculitis. The patient needed extensive workup and investigations to be eventually diagnosed with EGPA. In this case, myeloperoxidase (MPO) ANCA was negative, which is positive in the majority of EGPA cases, and this poses an additional diagnostic dilemma. Conclusion: The case highlights that non-specific complaints of vomiting and abdominal pain should be addressed methodically and not just be treated symptomatically.